2017
DOI: 10.1021/acs.jpcc.7b06199
|View full text |Cite
|
Sign up to set email alerts
|

Photocarrier Recombination and Injection Dynamics in Long-Term Stable Lead-Free CH3NH3SnI3 Perovskite Thin Films and Solar Cells

Abstract: We investigated the near-band-edge optical responses and photocarrier dynamics of encapsulated long-term stable CH 3 NH 3 SnI 3 (MASnI 3 ) thin films and solar-cell devices. The MASnI 3 thin film prepared with SnF 2 exhibited a bandgap of 1.25 eV, while the film without SnF 2 had a significantly blueshifted absorption edge. On the contrary, the PL peak energies were not influenced by the addition of SnF 2 . These observations indicate that the blueshift of the absorption edge in the SnF 2 -free MASnI 3 sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
114
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(130 citation statements)
references
References 56 publications
9
114
0
7
Order By: Relevance
“…Cahen and co‐workers found that SnF 2 can also increase the work function and ionization potential and enhance the stability of Sn‐based perovskites . In addition, SnF 2 was reported to increase the photocarrier lifetime and diffusion lengths of Sn‐based materials.…”
Section: Performance Of Sn‐based Perovskite Solar Cellsmentioning
confidence: 99%
“…Cahen and co‐workers found that SnF 2 can also increase the work function and ionization potential and enhance the stability of Sn‐based perovskites . In addition, SnF 2 was reported to increase the photocarrier lifetime and diffusion lengths of Sn‐based materials.…”
Section: Performance Of Sn‐based Perovskite Solar Cellsmentioning
confidence: 99%
“…(a) Reprinted with permission from [71], copyright 2017 American Chemical Society; (b) Reprinted with permission from [80], copyright 2017 American Chemical Society; (c) Reprinted with permission from [118], copyright 2017 American Chemical Society.…”
Section: Reviewmentioning
confidence: 99%
“…The main reason for such lowered performance is that tin‐based perovskites can easily become heavily p‐doped as a result of tin vacancy formation during synthesis or later degradation processes . As a result, charge‐carrier lifetimes are found to be lower than for lead‐based perovskites, leading to increased recombination losses, shortened charge‐carrier diffusion lengths, and dramatically decreased device performance …”
mentioning
confidence: 99%